2021
DOI: 10.15388/actpaed.2021.47.2
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Attitudes of Young Learners: Differences between Syrian Refugee Learners and Turkish Learners

Abstract: Welcoming more than 1.7 million refugee and asylum-seeker children, Turkey has put a considerable effort in turning this tragedy into an advantage for these children in terms of their education. Language teaching has played a remarkable role in this effort. Turkey has offered both Turkish and English language courses to these people. Considering the significance of English as a global language for social integration and future studies, this study attempted to investigate young Syrian refugee students’ attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, some studies conducted in the Asian context have explored children's perceptions of their motivations to learn English. In Turkey, Asmali [57] conducted a mixed-method study with 2nd-grade primary school students using questionnaires, interviews, and focus groups to explore their motivation and attitudes towards English language learning. The results revealed that most children felt highly motivated to learn and continue learning English.…”
Section: Recent Empirical Studies Of Motivation and Attitude Of Yllsmentioning
confidence: 99%
“…However, some studies conducted in the Asian context have explored children's perceptions of their motivations to learn English. In Turkey, Asmali [57] conducted a mixed-method study with 2nd-grade primary school students using questionnaires, interviews, and focus groups to explore their motivation and attitudes towards English language learning. The results revealed that most children felt highly motivated to learn and continue learning English.…”
Section: Recent Empirical Studies Of Motivation and Attitude Of Yllsmentioning
confidence: 99%
“…Compelling evidence has been documented to leave traces for those curious to elaborate on these detrimental factors for success in language learning. Students' backgrounds as refugees or members of other oppressed groups, in addition to their struggles with English language acquisition, become their own source of frustration (Asmali & Sayın, 2021;Ortega, 2021).…”
Section: Introductionmentioning
confidence: 99%